THE CONSTRUCTION OF INTERSTATE POLITICS IN THE RENAISSANCE: A CRITICAL REALIST ANALYSIS - TOPALOĞLU, Seyhan (SSD Journal, 2025)
This study examines the formation of the modern state and interstate politics during the Renaissance from a critical realist perspective. Critical realism enables the understanding of historical processes not merely through visible events and individual actors but through underlying structural mechanisms. The study analyzes the weakening of the Church’s authority and the transformation of intellectual climate as intrinsic factors in the formation of the modern state and the international system. Machiavelli’s concepts of virtù and fortuna provide a framework for understanding how notions such as raison d’état and jus gentium became sources of legitimacy. The dissolution of feudalism, the rise of the bourgeoisie, and the emergence of the secular state were shaped not only by political and economic transformations but also by shifts in the epistemological frameworks that produced knowledge. This study argues that the Renaissance was not merely an intellectual rebirth but a multilayered process in which new forms of domination were produced and the foundations of the modern international system were laid. In this context, the study also questions whether the Renaissance constitutes an epistemological fallacy, advocating for its analysis not only through a progressivist historical narrative but also within the ruptures created by social and political transformations.